DASAR-DASAR MANAGEMEN ORGANISASI - Afrahul Fadhila Daulai (Universitas Islam Negeri Sumatera Utara Medan, 2016)
In the world of education, the management is also very important to set each school, especially between the committee, the principal, staff, educators and learners so that input and output is completely grade school. Each of these elements does not stand alone but interrelated and influence each other. In this paper not all elements of management functions discussed but focused on aspects of the organization only.Keywords: Dasar-dasar Managemen, Organisasi.